2019
DOI: 10.1002/sia.6652
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of surface characteristics of two industrial 7xxx aluminium alloys exposed to humidity at moderate temperature

Abstract: This study analyses the evolution of surface characteristics of two industrial high‐strength 7xxx aluminium alloys with a focus on alloy composition and environmental parameters. Based on storage and transport conditions of as‐machined products, the effect of humidity—as liquid and vapour phase—on the natural oxide layer has been studied. The evolution of the natural oxide layer has been analysed by scanning electron microscopy and X‐ray photoelectron spectroscopy. The growth behaviour of the surface layer is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A two-layer structure appears, with first a ~5 nm zone enriched in Mg and O, followed by a region with increased Zn and lower in O and Mg. O/H increase again further ahead, but Mg and Zn do not show increased levels. The formation of an Mg-rich oxide film in aluminium alloys was suggested by Green et al 38 and reported experimentally 39 , 40 . The oxide film is also found to be hydrated, which is in line with previous observations 3 , 39 , 41 .…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…A two-layer structure appears, with first a ~5 nm zone enriched in Mg and O, followed by a region with increased Zn and lower in O and Mg. O/H increase again further ahead, but Mg and Zn do not show increased levels. The formation of an Mg-rich oxide film in aluminium alloys was suggested by Green et al 38 and reported experimentally 39 , 40 . The oxide film is also found to be hydrated, which is in line with previous observations 3 , 39 , 41 .…”
Section: Resultsmentioning
confidence: 82%
“…The formation of an Mg-rich oxide film in aluminium alloys was suggested by Green et al 38 and reported experimentally 39 , 40 . The oxide film is also found to be hydrated, which is in line with previous observations 3 , 39 , 41 . Levels of Cl of up to 14 at.%, not included in the profiles for clarity, are also incorporated in the oxide film, as expected 4 .…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…In the process of rolling, the embrittlement would result in cracks in the middle of the magnesium alloy that affects the quality of the magnesium alloys [31][32][33]. erefore, it is necessary to dehumidify in the rolling environment [34,35].…”
Section: Introductionmentioning
confidence: 99%